Effect of management practice and age on increment in Pinus patula plantations in Nepal - Dangal, S. P.; Das, A. K. (Banko Janakari, 2018)
With the large-scale plantation commenced in the early 1980s, nearly 370,000 hectares of plantations have been successfully established in Nepal. More than 26 thousand hectares (ha) of plantations have been established since late seventies in Sindhupalchok and Kavrepalanchok districts and are handed over to communities as community forests. Pinus roxburghii and Pinus patula are the dominant species of these plantations aiming to maximize biomass productions and restore greenery in degraded hills. The growth rate Pinus patula was estimated 15 m³ ha-1 yr-1 in 1995 which but reduced to 7 m³ ha-1 yr-1 in 2011. As P. patula is an exotic species to Nepal, knowledge on effect of age and management practices on increment was limited in Nepal as well as in the regions. This is hindering in implementations of appropriate silviculture by the forest managers. To fill this knowledge gap, primary data were collected taking sample cores from 120 trees in 2015 from four community forests of Chaubas ridge of Kavrepalanchok district for dendrochronological assessment. Among these four community forests, two followed improved management practices and two followed conventional management practices. To substantiate the data, secondary data of similar studies were used. Dendrochronological assessment taking sample cores of 120 and 80 were conducted in 2000 and 2005 respectively in plantations, managed by community forest users groups, carried out between 1975 AD and 1990 AD in Chaubas ridge of Kavrepalanchok districts. The study found that the growth rate decreased after 12 years and this rate was bigger in the higher density class. The cumulative increment was higher in the lower density class but was found to have retarded rapidly after 15–17 years of age in the higher density class as well as in the conventionally managed plantations. The study recommends conducting planned thinning from the early age of 10–12 years while the final felling is recommended to be executed at the age of 30±5 years for P. patula to maximize volume production. However, most of the plantations have crossed its rotation age, growth rate has been stagnated and there is slim scope of increment from further thinning. In such case, as natural regeneration of the same species is observed encouraging, the study suggest to keep 10–15 seed trees and harvest the remaining. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page : 27-37